What's wrong with 'expeditioner'? - Leane, E; Philpott, C (Polar Record, 2016)
2016 Cambridge University Press.Some-particularly Australasian-authors who have published in Polar Record may be familiar with the debate around the acceptability of the word 'expeditioner'. The term is regularly used by Australians and New Zealanders, in both casual and official contexts. In The Antarctic Dictionary, Bernadette Hince (herself Australian) classifies the word as particularly (although not solely) Australian, notes its regular use by the Australian national programme, which publishes an Expeditioner Handbook, and defines it as 'A member of an [A]ntarctic expedition, including a government expedition' (Hince 2000: 118-119). However, 'expeditioner' appears in the Oxford English Dictionary only as a rare and obsolete term. The sole example cited in the OED Online is from 1758, in a non-polar context; the definition provided is 'One engaged in an expedition'. Neither The Australian Oxford Dictionary (2nd edition, 2004) nor The New Zealand Oxford Dictionary (2005) includes 'expeditioner', although the term is included in the Australian Macquarie Dictionary (5th edition, 2009) and the US-based Webster's Third New International Dictionary (1993). There is clearly significant national variation in the term's acceptability and its use in an academic publication can draw negative attention (Stone 2003: 172-not coincidentally, a British review of a book by an Australian author). This note argues that 'expeditioner' should not be dismissed as an idiolectic ungrammatical term unsuitable for use in British publications. We make a case for the use of 'expeditioner' on three grounds: conceptual appropriateness, precedence and convenience of expression.